Progressive Facial Haemiatrophy (Parry-Romberg Syndrome) Treated with Hyaluronic Acid Fillers - Luciana Yacomotti; Daniel Alejandro Muszalski; Maria Cecilia Miksa; Sofía Duran; Natalia De Magistra; Victor Castilla (European Medical Journal, 2023)
Introduction: Parry-Romberg syndrome (PRS) is a rare neurocutaneous condition that can affect the skin, subcutaneous fat, muscle, and bone on one side of the face. PRS presents with progressive but self-limiting facial haemiatrophy, and its severity ranges from barely noticeable asymmetry to severe disfigurement. The authors describe a 35-year-old male with right facial haemiatrophy. The patient presented in a stable condition at the initial consultation. Objectives: Adipose tissue autografts were the most used tool to treat many congenital or acquired facial deformities. The authors proposed using cross-linked hyaluronic acid (HA) fillers over those traditionally used to correct facial deformities due to PRS. Discussion: PRS is usually self-limiting, with the maximal progression of the disease 2-5 years after onset. There is no specific cure for PRS at present. After 7 years of progression from the onset, this patient entered a stable phase. Reconstructive treatment was then indicated, since there were no further signs of atrophy. Since adipose tissue autografts require complicated surgical skills, which take a lot of time and cost, the authors report a case of PRS augmented by HA filler in a 35-year-old male patient to suggest that HA filler could be a safe and simple alternative to surgical treatment. The authors conclude that HA fillers are a safe tool for treating facial deformities in patients with PRS.